2021
DOI: 10.3389/fphar.2021.736442
|View full text |Cite
|
Sign up to set email alerts
|

Taxus wallichiana var. chinensis (Pilg.) Florin Aqueous Extract Suppresses the Proliferation and Metastasis in Lung Carcinoma via JAK/STAT3 Signaling Pathway

Abstract: As one of the most common neoplasms globally, lung cancer (LC) is the leading cause of cancer-related mortality. Recurrence and metastasis negatively influencing therapeutic efficacy and overall survival demand new strategies in LC treatment. The advantages of TCM are increasingly highlighted. In this study, we obtained the major chemical components and their ratios in the aqueous extract of Taxus wallichiana var. chinensis (Pilg.) Florin (AETW) by UPLC-Q/TOF-MS/MS detection. The CCK-8 assay revealed that AETW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The UPLC and MS conditions have been developed and validated based on our previously reported protocols with some modifications. 15 A Waters Acquity UPLC system (MA, USA) and a CORTECS ® UPLC ® C18 column (2.1 mm × 100 mm, 1.7 μm) were applied to the chromatographic separation of QBD. The mobile phase was composed of 0.1% formic acid water solution (mobile phase A) and acetonitrile (mobile phase B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UPLC and MS conditions have been developed and validated based on our previously reported protocols with some modifications. 15 A Waters Acquity UPLC system (MA, USA) and a CORTECS ® UPLC ® C18 column (2.1 mm × 100 mm, 1.7 μm) were applied to the chromatographic separation of QBD. The mobile phase was composed of 0.1% formic acid water solution (mobile phase A) and acetonitrile (mobile phase B).…”
Section: Methodsmentioning
confidence: 99%
“…The UPLC and MS conditions have been developed and validated based on our previously reported protocols with some modifications. 15 A Waters Acquity UPLC system (MA, USA) and a CORTECS ® UPLC ® C18 column (2.1 mm × A Waters Xevo QTS MS/MS (MA, USA) with an electron spray ionization (ESI) source was used for MS detection in both positive-and negative-ion modes. The optimized mass parameters were set as follows: full scan range: (m/z 100-1500), argon as collision gas, and nitrogen as nebulizer and heater gases (500 L/h).…”
Section: Uplc-q/tof-ms/ms Conditionsmentioning
confidence: 99%
“…Additionally, the CCK-8 assay showed that TAE has a selective inhibitory effect on the growth of non-small cell lung cancer A549 and HCC827 cells and is dose-dependent, with minimal impact on everyday human lung cells. Its mechanism may be related to inhibiting tumor cell proliferation and metastasis by inactivating the JAK/STAT3 axis [ 77 , 78 ]. Research also indicated that taxane compounds extracted from T. mairei exhibit a specific inhibitory effect on the proliferation of A549 non-small cell lung cancer cells (IC50 between 26–167 μg/mL).…”
Section: Pharmacological Activity Studiesmentioning
confidence: 99%
“…Many studies have confirmed that PTX inhibits the growth of a variety of tumors [55]. The main mechanism of action for PTX is to cause abnormal arrangement of microtubules and the production of microtubule stellates during cell proliferation to hinder cell amplification, inhibit tumor growth and proliferation, induce apoptosis, and enhance innate immunity [56].…”
Section: Paclitaxel (Ptx)mentioning
confidence: 99%